2022
DOI: 10.3897/zookeys.1087.76668
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of Tylos maindroni Giordani Soika, 1954 (Crustacea, Isopoda, Oniscidea) based on SEM and molecular data

Abstract: The woodlouse species Tylos maindroni Giordani Soika, 1954 (Crustacea, Isopoda, Oniscidea) is redescribed from the Persian Gulf based on light and scanning electron microscopy. This species differs from the closely related T. exiguus Stebbing, 1910, from the Red Sea (coasts of Sudan and Eritrea), and Socotra Island, by pereopod 1 superior margin without a prominent projection and pleopod 2 endopod 2.3 times as long as exopod, vs. 3.6 in T. exiguus. A distribution map for T. maindroni is provided. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A scanning electron microscopy image in Figure shows a species of woodlouse, Tylosmaindroni Giordani Soika. [ 102 ] A variety of periodic structures are located on different parts of the body, at the same distance from one another. The structural forms are spherical, porous, and conical sub‐wavelength structures, as well as cylindrical structures connected in a row of 3–4 cylinders and located in the same direction.…”
Section: Future Directionmentioning
confidence: 99%
See 1 more Smart Citation
“…A scanning electron microscopy image in Figure shows a species of woodlouse, Tylosmaindroni Giordani Soika. [ 102 ] A variety of periodic structures are located on different parts of the body, at the same distance from one another. The structural forms are spherical, porous, and conical sub‐wavelength structures, as well as cylindrical structures connected in a row of 3–4 cylinders and located in the same direction.…”
Section: Future Directionmentioning
confidence: 99%
“…The structural forms are spherical, porous, and conical sub‐wavelength structures, as well as cylindrical structures connected in a row of 3–4 cylinders and located in the same direction. [ 102 ] On some surfaces, several sub‐wavelength structures appear at once, most likely due to other properties in addition to anti‐reflection.…”
Section: Future Directionmentioning
confidence: 99%
“…A mitochondrial gene, cytochrome c oxidase I (COI), has been identified as an available sequence in species delimitation [ 4 , 5 , 6 ]. Park et al, 2011 found that for the researched 344 heteropteran species which applied DNA barcoding, the minimum interspecific distances exceeded 3% in 77% of congeneric species pairs [ 7 ].…”
Section: Introductionmentioning
confidence: 99%